Using an Evidence-Based Approach to Design Large-Scale Programs to Improve Infant and Young Child Feeding. Issue 3 (September 2013) - Baker, Jean; Sanghvi, Tina; Hajeebhoy, Nemat; Martin, Luann; Lapping, Karin
Background: Global interest in scaling up nutrition outcomes has focused attention on the need for more effective programs to improve infant and young child feeding (IYCF). However there are few examples in the literature of comprehensive programs that have been systematically designed. Objective: To describe an evidence-based approach for designing large-scale yet tailored IYCF programs in varied country settings. Methods: Behavior change principles, epidemiological data, situational analysis, stakeholder consultations, formative research, and feasibility studies informed the design of IYCF programs delivered at scale in Bangladesh, Ethiopia, and Vietnam. Results: Impact, scale, and sustainability objectives guided the choice of partners, service delivery platforms, and advocacy, systems strengthening, and communication strategies for reaching mothers and decision makers. All programs focused on the critical first 2 years of life, followed global World Health Organization and UNICEF guidelines for IYCF, and applied a common theory of change. Formative research, stakeholder consultations, trials of improved practices, and assessments of media habits were most useful for making program decisions. Opinion leader research, monitoring of the policy environment, and stakeholder analysis were key elements in the design of advocacy strategies. All programs found that setting measurable and explicit targets, strengthening systems to provide support for mothers, multichannel communication, and advocacy for opinion leaders were vital components in the design. Conclusions: A systematic, evidence-based collaborative approach can facilitate the design of comprehensive IYCF programs. Programs should also embed design flexibility to enable changes as new challenges and opportunities arise.